Morphological variation and its correlation with bioclimatic factors in Odorrana graminea sensu stricto - Li, Hanyu; Cui, Chong; Shen, Huijun; Zhu, Yanjun; Chen, Zhuo; Chen, Xiaohong (Frontiers in Ecology and Evolution, 2023)
The large green cascade frog (Odorrana graminea sensu stricto) shows significant genetic differentiation in China, forming western, southern, and eastern clades. However, the morphological differentiation among the three clades is unclear, and the influence of bioclimate factors on morphological variation among clades is unknown. Based on 20 morphological traits of 309 specimens from 28 localities, we explored the morphological differentiation and variation among clades and its correlation with bioclimatic factors through multivariate statistical analysis. The results showed that O. graminea sensu stricto was divided into western, southern, and eastern morphological groups, and gene flow between neighboring populations had caused individual misidentification. With the three-step terrain and population distribution latitude and humidity, the annual mean temperature (Bio1) was significantly different between the southern and eastern-western clades; the maximum temperature of the hottest month (Bio5) was significantly different between the southern and western clades, and the mean temperature of the wettest quarter (Bio8) and the precipitation seasonality (Bio15) were significantly different between the eastern and western-southern clades. The southern clade affected by high temperature had smaller body size and larger sensory organs, and the eastern clade distributed in highly humid areas had larger body size and smaller sensory organs. Moreover, the annual mean temperature range (Bio7) was the dominant factor in the morphological variation of O. graminea sensu stricto, and it had significant negative correlations with seven traits of males and four traits of females. The effect of precipitation factors on morphological differentiation of each clade remained unclear. The local adaptation caused by climate differences was the main reason for the morphological differentiation among clades. These findings will help us to understand amphibians' abilities to adapt to environmental variation.